Pengendalian Kualitas Telur Dengan Metode Seven Tools di Umkm Puyuh Kompas - Salsabilla Maylenia Manaf; Rizki Achmad Darajatun (Jurnal Ilmiah Wahana Pendidikan, 2022)
Every business must have their own standards for the products they produce. The better the quality of the product, the more sales the product will sell. One way to improve product quality is to reduce the defects of the resulting product so that later it will produce a better product than before. Quail is a poultry that has been bred a lot because of high egg production, because it is still a medium business, it is still necessary to control the quality of food and nutrition obtained in order to improve the quality of quail eggs. It is done by using seven tools method, namely check sheet, histogram, scatter diagram, Pareto diagram, control chart, flow chart, and fishbone diagram. Data taken in 4 weeks showed that the number of eggs produced was 5953 along with defective eggs. Based on the data taken, there are 3 types of defective eggs, namely cracked, broken and soft shell. Based on the fishbone diagram, human factors also affect egg quality.